ANALISIS PENAMBAHAN ABU BATU TERHADAP KUAT TEKAN PAVING BLOCK - Monica Sagay; Rifana Kawet; Titof Tulaka, (Sustainable Construction (SUSCON), 2024)
Paving blocks (concrete bricks) are a building material composition made from a mixture of Portland cement or similar hydraulic adhesive, water, and aggregate with or without other added ingredients. This research was conducted to find out whether the use of stone ash as an additional ingredient in the mixture for making paving blocks can increase the compressive strength of paving blocks using a manual paving block molding tool. The method used in this research is an experimental method carried out at the Materials Technology Laboratory, Faculty of Engineering, Manado State University by carrying out a series of sample tests. The results of research that has been carried out regarding the manufacture of paving blocks with the addition of stone ash with the aim of increasing the compressive strength value of paving blocks can be concluded that, paving blocks with the addition of stone ash as much as 15%, 25%, 35% and 50% respectively experienced a decrease which is very significant when compared to normal paving blocks or without the addition of stone ash.